2022
DOI: 10.3847/1538-4357/ac4bba
|View full text |Cite|
|
Sign up to set email alerts
|

Robust Absolute Solar Flux Density Calibration for the Murchison Widefield Array

Abstract: Sensitive radio instruments are optimized for observing faint astronomical sources, and usually need to attenuate the received signal when observing the Sun. There are only a handful of flux density calibrators that can comfortably be observed with the same attenuation setup as the Sun. Additionally, for wide field-of-view (FoV) instruments like the Murchison Widefield Array (MWA) calibrator observations are generally done when the Sun is below the horizon, to avoid the contamination from solar emissions. Thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…We find that inter-picket bandpass phases for MWA can be modelled well by a straight line (Sokolowski et al 2020). Inter-picket bandpass amplitudes show a more complicated variation and are corrected using an independent method described by Kansabanik et al (2022).…”
Section: Bandpass Self-calibrationmentioning
confidence: 81%
See 4 more Smart Citations
“…We find that inter-picket bandpass phases for MWA can be modelled well by a straight line (Sokolowski et al 2020). Inter-picket bandpass amplitudes show a more complicated variation and are corrected using an independent method described by Kansabanik et al (2022).…”
Section: Bandpass Self-calibrationmentioning
confidence: 81%
“…Antennas at larger distances are progressively added. The process of intensity self-calibration with increasing number of distant antennas is similar to that implemented in AIRCARS (Mondal et al 2019) success has already been demonstrated by many studies relying on high dynamic range imaging (e.g, Mohan et al 2019b,a;Mondal et al 2020b,a;Mohan 2021a,b;Kansabanik et al 2022).…”
Section: Intensity Self-calibrationmentioning
confidence: 96%
See 3 more Smart Citations